Current trends in the pharmacotherapy of uterine myoma, associated with heavy menstrual bleeding and anemia: a literature review - Z. V. Revazova; L. V. Adamyan; O. N. Loginova; L. M. Manukyan; K. N. Arslanyan (IRBIS LLC, 2021)
Aim: to summarize up-to-date world data on current opportunities of drug therapy in treatment of symptomatic myoma accompanied with heavy menstrual bleeding and anemia.Materials and Methods. A search of publications was carried out in the main international databases published in Russian and English: PubMed/MEDLINE, The Cochrane Library, Embase, and eLibrary. The analysis included studies published over the last 10 years examining the clinical efficacy and safety of various groups of pharmacological agents used for treatment of uterine myoma combined with heavy menstrual bleeding in women of reproductive age.Results. Currently, treatment of uterine fibroids consists of the three major approaches: surgical, minimally invasive organpreserving methods, and pharmacotherapy. Until now, surgical intervention remains the main method of treatment, unfortunately being often performed in a foem of hysterectomy. However, today it is important to apply a personalized approach to the management of a female patient with symptomatic uterine myoma, taking into account her wish to preserve reproductive function. Advances in drug therapy greatly contributed to optimizing management of such patients.Conclusion. Treatment of symptomatic uterine fibroids globally tends to lowering the number of radical interventions, as well as develop and improve new therapeutic approaches for. Currently, pharmacotherapy of leiomyoma can substantially improve the quality of patients' life, lower number of radical surgical interventions, optimize surgical treatment, and even fully negate, in some cases, a need for surgery.